A Research On Information System Audit In Manufacturing Environment - Singaraju, Ramesh (2006)
This research study is aimed to discover a standard audit method which suites the manufacturing environment. Thus, this research has led to the implementation of IT audit method by using the Control Objective for Information and related Technology (COBIT) standard to help Samsung Corning (M) Sdn Bhd in meeting the multiple needs of management by bridging the gaps between business risks, control needs and technical issues.